Design and Kinematic Analysis of Rod Gear Reducer and Transmission - Zhai Guodong; Li Zhen; Zhou Youqiang; Ai Chunpei; Lan Yu; Zang Fuyu (Jixie chuandong)
Rod gear speed reducer and transmission is composed of linkage mechanism and meshing transmission. This transmission mechanism is simplified plane four-bar mechanism. On the basis of kinematics and geometry principle,the kinematics analysis of the mechanism is studied by means of matrix method. The corresponding kinematics equations are derived,including position,velocity and acceleration equations of rod and rockers. The computer simulation analysis is developed and the variation curve of main component angle displacement,angle velocity,angle acceleration and errors are figured by using MATLAB program language. This study laid a foundation for further analysis and optimization of the rod gear speed reducer and transmission.